A 'Problem of Fairness' in the Making: The Transformation of Public Services from the Perspective of Postal Workers. (27th January 2016) - Flecker, Jörg; Schultheis, Franz; Vogel, Berthold
Abstract: During the last two decades public administration and public services have undergone profound changes with far‐reaching impacts on employment relations and working conditions. The paper presents the perceptions and lived experiences of workers affected by liberalization and privatization of public services. In doing so it focuses on workers' ideas of fairness and dignity at work using the concepts of distribution, recognition and the public ethos of the common good and linking them to fundamental principles of justice. It is argued that the perception of inequalities as fair, while it is shaped by custom, is also being socially constructed during far‐reaching changes. The analysis is based on a series of qualitative interviews conducted in Austria, Germany and Switzerland with postal‐service workers, a sector well suited for the analysis because of the far‐reaching changes in terms of market regulation, ownership of organizations, labour regulation, employment and working conditions.